2020
DOI: 10.1007/s11357-020-00160-w
|View full text |Cite
|
Sign up to set email alerts
|

Age-related changes in the cartilage of the temporomandibular joint

Abstract: Osteoarthritis (OA) of the knee is closely associated with aging; however, little is known about the age-related degeneration in the mandibular condylar cartilage (MCC) of the TMJ. Our objective was to examine whether a correlation exists between aging and degeneration of the MCC of the TMJ. Thirty-two male C57BL/6J wild-type mice were aged to 2, 12, 18, and 25 months old. The mice were euthanized by CO 2 inhalation and were dissected and examined by micro-CT and histology. Sagittal sections of the condyles we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 33 publications
4
21
0
Order By: Relevance
“…It is still unclear how D+Q increases cartilage thickness and bone turnover (increased AP and TRAP signals) in old TMJs. We found that Bmp2 level increased with aging (consistent with previous findings (Chen et al, 2020)), while DQ has little effect on Bmp2 level in either young or old TMJs (Figure 1a), indicating that D+Q might not work through Bmp2 pathway. Future experiments are needed to further investigate these underlying mechanisms.…”
Section: Figuresupporting
confidence: 92%
See 4 more Smart Citations
“…It is still unclear how D+Q increases cartilage thickness and bone turnover (increased AP and TRAP signals) in old TMJs. We found that Bmp2 level increased with aging (consistent with previous findings (Chen et al, 2020)), while DQ has little effect on Bmp2 level in either young or old TMJs (Figure 1a), indicating that D+Q might not work through Bmp2 pathway. Future experiments are needed to further investigate these underlying mechanisms.…”
Section: Figuresupporting
confidence: 92%
“…Notably, we observed that D+Q increased cartilage thickness by more than 30% in old TMJs within 5–8 weeks (Figure 2b). Since TMJ cartilage thickness declines gradually with aging (Chen et al, 2020), our data support less degeneration with DQ treatment and plausible reasons could be regeneration or prevention of degeneration of the TMJ cartilage. This could be clinically significant, since the current barrier to success in TMJ degeneration treatment is that TMJs fail to regenerate the diseased cartilage tissue that could recapitulate the cellular composition, structure, and load‐bearing capacity of healthy joint cartilage.…”
Section: Figuresupporting
confidence: 73%
See 3 more Smart Citations